SMART: Self-Management of Anticoagulation, a Randomised Trial [ISRCTN19313375] - McCahon, D; Fitzmaurice, D; Murray, E; Fuller, C; Hobbs, R; Allan, T; Raftery, J (BioMed Central, 2003)
Background: Oral anticoagulation monitoring has traditionally taken place in secondary care because of the need for a laboratory blood test, the international normalised ratio (INR). The development of reliable near patient testing (NPT) systems for INR estimation has facilitated devolution of testing to primary care. Patient self-management is a logical progression from the primary care model. This study will be the first to randomise non-selected patients in primary care, to either self-management or standard care. Method: The study was a multi-centred randomised controlled trial with patients from 49 general practices recruited. Those suitable for inclusion were aged 18 or over, with a long term indication for oral anticoagulation, who had taken warfarin for at least six months. Patients randomised to the intervention arm attended at least two training sessions which were practice-based, 1 week apart. Each patient was assessed on their capability to undertake self management. If considered capable, they were given a near patient INR testing monitor, test strips and quality control material for home testing. Patients managed their own anticoagulation for a period of 12 months and performed their INR test every 2 weeks. Control patients continued with their pre-study care either attending hospital or practice based anticoagulant clinics. Discussion: The methodology used in this trial will overcome concerns from previous trials of selection bias and relevance to the UK health service. The study will give a clearer understanding of the benefits of self-management in terms of clinical and cost effectiveness and patient preference.